The Influence of Walk on Decreasing Blood Pressure in Hypertension Patients - Triana Arisdiani; Ahmad Asyrofi; Rizka Nurul Izza (Global Health Science Group, 2023)
The number of incidents in people with hypertension lacks physical activity resulting in complications of hypertension such as heart disease, kidney failure and stroke. Efforts that can be made to lower blood pressure with non-pharmacological therapy are walking because it can control blood pressure. This study aims to determine the effect of walking on pressure reduction in hypertensive patients. Methods: The research design uses a Quasi Experiment with a Pre-test Post-test Control Group Design approach. The number of samples was 68 consisting of 34 control groups and 34 walking intervention groups taken by consecutive sampling. The instruments used were observation sheets, calibrated sphygmomanometers, stopwatches, and standard operating procedures (SOP) for walking. Data analysis used Wilcoxon test and Mann-Whitny test. Results:Results of Mann-Whitny test analysisshows that there is an effect of walking on systolic and diastolic blood pressure with valueρvalue< 0.05. Discussion: It is hoped that people with hypertension can practice walking because walking has a positive effect on the body to help smooth blood flow throughout the body and increase the elasticity of blood vessels so that the heart works more effectively and blood pressure decreases to near normal.